Infrastructure and Inequality: Insights from Incorporating Key Economic Facts about Household Heterogeneity - David Klenert; Linus Mattauch; Ottmar Edenhofer; Kai Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the trade-off between equity and growth in the context of tax-financed investment in public capital. Taking into account stylized facts on wealth accumulation, we model agent heterogeneity through differences in saving behavior, income source and time preference. In contrast to the results of studies that introduce heterogeneity through different initial endowments only, we find that under our heterogeneity assumptions an equity-efficiency trade-off does not necessarily occur. We show that a consumption tax or a capital tax, levied to finance public capital, does not increase inequality. In our model capital tax-financed public investment has even an inequality-reducing effect - thus allowing for Pareto-improving public investment that decreases inequality. Additionally we find that agents differ in their preferred tax rates. These results are valid for both, the case of endogenous growth and the case of steady state convergence and do not require the assumption of an identical rate of pure time preference across all households.
Keywords: E21; E60; H23; H31; H54; 330